Monetary policy transmission and house prices : European cross-country evidence - Kai Carstensen; Oliver Hülsewig; Timo Wollmershäuser (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper explores the importance of housing and mortgage market heterogeneity in 12 European countries for the transmission of monetary policy. We use a panel VAR model which is estimated over the period 1995-2006 to generate impulse responses of key macroeconomic variables to a monetary policy shock. We propose a data-driven approach that splits our panel of countries into two disjoint groups according to the impact of the monetary policy shock on real house prices. Our results show that in countries with a more pronounced reaction of real house prices the propagation of monetary policy shocks to macroeconomic variables is amplified.
Keywords: C32; C33; E52; 330; panel VAR model; house prices; monetary policy transmission; country clusters; sign restrictions; Geldpolitik; Schock; Transmissionsmechanismus; Immobilienpreis; Hypothek; Kreditmarkt; Immobilienmarkt; EU-Staaten